Auditory Manifestations of Vestibular Migraine - Shi, Suming; Wang, Dan; Ren, Tongli; Wang, Wuqing (Frontiers in Neurology, 2022)
Objectives: To investigate the auditory features of patients with vestibular migraine (VM) and to analyze the possible relevant factors of hearing loss. Methods: A total of 166 patients with VM were enrolled. Demographic variables, age of onset, disease course, distribution of vestibular attacks, characteristics of hearing loss, the coexistence of related disorders such as visual aura, familial history, motion sickness, nausea, headache, photophobia, otalgia, tinnitus, aural fullness and phonophobia were analyzed and compared. Results: Patients with VM can manifest as otalgia (8.4%), tinnitus (51.8%), aural fullness (41.0%) and phonophobia (31.9%). Of 166 patients, the prevalence of VMw was 21.1% (n=35). Patients with VMw were mainly manifested as mild and easily reversible low-frequency hearing loss. The proportions of tinnitus and aural fullness were significantly larger in patients with VMw than that in patients with VMo (P < 0.05). The duration of vestibular symptoms was significantly shorter in patients with VMw (P < 0.05). However, the age of onset, disease course, gender, frequency of vestibular attacks, the coexistence of visual aura, familial history, motion sickness, nausea, headache, photophobia, otalgia and phonophobia had no significant difference between two groups. Conclusions: Auditory symptoms were common in patients with VM. For the hearing loss of VM, it was characterized by a mild and easily reversible low-frequency hearing loss, accompanied by higher proportions of tinnitus and aural fullness, and a shorter duration of vestibular symptom compared with patients with VMo.